Investigation about the perceptions and strategies adopted by argentinean teachers to approach the theme “health” at school (Research, Society and Development, 2021)
Objective: to investigate the concepts of “Health” and the strategies used by teachers for the work on health at school. Methodology: this is a qualitative research carried out with Portuguese-speaking teachers from the province of Corrientes / Argentina. The activities were divided into stages: i) application of an initial questionnaire; ii) teacher training; and iii) reapplication of the initial questionnaire. This research was approved by the Research Ethics Committee of the Federal University of Rio Grande do Sul, under the Certificate of Presentation of Ethical Appreciation 19717619.1.0000.5347. Results: 51 teachers participated, with an average age of 41 years. It was possible to observe that, after training, teachers expanded their health concepts, starting to consider other aspects besides the purely biomedical concept. The teachers also rated the training as good / excellent. Final Considerations: the training enabled teachers to broaden their health concepts and discover new possibilities to address this issue in the classroom. It is suggested that further research like this be carried out in different countries, especially those belonging to MERCOSUR.